Factors associated with the level of knowledge about exclusive breastfeeding in first mothers served by teleconsultation – National Maternal Perinatal Institute in 2020 - Vizquerra-Guevara, Pablo (2021)
Objective: To determine the factors associated with the level of knowledge about exclusive breastfeeding in first-time mothers attended by teleconsultation of the National Maternal-Perinatal Institute in 2020. Materials and methods: Study with a quantitative approach, descriptive, observational, cross-sectional, and analytical design. The population was made up of a total of 1000 primiparous mothers attended by teleconsultation at the National Maternal Perinatal Institute, taking a representative sample of 240. A reliable and valid instrument was used to measure knowledge in exclusive breastfeeding, statistical association tests were performed and bivariate and multiple Poisson regression model to obtain the raw and adjusted prevalence ratio and their 95% confidence intervals for the associated factors and exclusive breastfeeding categories. Results: a high 75.7% level of knowledge about exclusive breastfeeding was found, with a 95% CI of 69.5% - 81.1%. A statistically significant association was found for the variables of the elderly pregnant woman (PRa 1.21 95% CI 1.05 - 1.39) and higher education level (PRa 1.22 95% CI 1.02 - 1.44). Conclusions: a high level of education and elderly pregnancy were identified as associated factors at a high level of knowledge about exclusive breastfeeding in primiparous mothers attended by teleconsultation from the National Maternal-Perinatal Institute in 2020.